Supporting the pilot low methane emission for rice at the Qingshan Village - Zhen, Yan; Yang, Xiaoneng (CGIAR System Organization, 2025)
Rice is one of China’s three major staple food crops, accounting for approximately 60% of total staple food consumption, and rice paddies are among the largest emission sources in China’s crop production systems. According to statistics from the Food and Agriculture Organization of the United Nations (FAO), China ranked first globally in total rice production in 2022, with output exceeding 210 million tons, accounting for 28.0% of global rice production. The rice planting area reached nearly 450 million mu, representing 18.5% of the global rice planting area, second only to India. Meanwhile, global carbon emissions from rice paddies account for about 52% of total emissions from croplands, and in China, rice paddy emissions contribute approximately 60% of emissions from the crop production sector, with methane being the dominant greenhouse gas. China attaches great importance to agricultural carbon sequestration and emission reduction, and in recent years has successively issued policy documents such as the “Action Plan for Carbon Peaking Before 2030”, the “14th Five-Year National Plan for Green Agricultural Development”, the “Technical Guidelines for Green Agricultural Development (2018-2030)”, and the “Implementation Plan for Emission Reduction and Carbon Sequestration in Agriculture and Rural Areas”, all of which emphasize the critical role of agriculture in carbon mitigation. Therefore, under the context of global climate change, how to reduce carbon emissions from rice production has become a key issue of widespread concern in both the scientific community and society at large.